Magnetic nanoparticles and nanocomposites in diagnostics and treatment of diseases - Turanskaya, S. P.; Turov, V. V.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
The review is made on the development and use of magnetic nanocomposite materials, which are perspective for target drug delivery, hyperthermia, as contrasting agents in magnetic resonance imaging, in immunotests and for the purification or separation of different bioobjects.